The AnalysisÂ Prospects for Future Development of Silk SariÂ because of Agrotourism Activities, Abiansemal, Badung - Mutria Farhaeni; Elsita Lisnawati Guntar; Sri Martini (Universitas Warmadewa, 2022)
This study aims to analyze the prospects and strategies for future development of Silk Sari Segara Agrotourism, the obstacles faced. The method used was interviews with a purposive sampling approach to determine key informans, followed by the snowball method to obtain as much data and information as possible from other informants. From the results of the interview, it was then studied using a SWOT analysis and narrated in descriptive form. The results of this study revealed that the prospects and future development strategies of the Sari Segara silk agro tourism activity have the potential to be developed in the world of tourism in Bali which has a variety of businesses, especially in the process of quantity, quality of production and marketing which is carried out with traditional looms besides that it is very useful to use. Weaving processes that still use non-machine weaving tools (ATBM), namely in the form of traditional weaving tools as a superior activity of local wisdom. Thus, support from the government and the private sector are needed to help facilitate, market and support the surrounding communities. Signs are needed to prevent environmental damage and pollution. It needs to be socialized to silkworm breeders in order to maintain the balance of environment. Entrepreneurs/managers are expected to maintain harmony and culture in the community around the agro-tourism business site. The constraints faced in managing agro-tourism businesses today must be immediately addressed so that the quality of production can compete both nationally, regionally and internationally and sustainable.